The Dynamics, Challenges, and Strategic Opportunities of Solar Energy Development in the South Caucasus Countries - Markosyan, Meruzhan; Matevosyan, Elyanora; Markosyan, Ashot (Journal of Environmental Accounting and Management, 2026)
This study assesses the dynamics and opportunities of solar energy development in the three South Caucasus countries---Armenia, Azerbaijan, and Georgia---during 2018--2024. The region shows a clear upward trend in solar deployment, albeit at different speeds. Armenia expanded installed PV capacity from 17.3 MW to 485.4 MW (CAGR $≈$ 74%/yr), Azerbaijan from 34.9 MW to 292.9 MW (CAGR $≈$ 43%/yr; acceleration after 2022), and Georgia from 0.9 MW to 132.6 MW (CAGR $≈$ 130%/yr, small-base effect). Growth is shaped by policy clarity, investment risk allocation, grid-integration readiness, and access to technology. The mixed-methods approach combines quantitative indicators (installed capacity, compound annual growth rates) with a structured qualitative review of policies and market rules. We complement country analysis with comparative views across former Soviet states and neighboring systems (Türkiye, Iran). Case notes (e.g., Masrik-1 in Armenia; Jabrayil/Shafag in Azerbaijan) illustrate utility-scale deployment and bring performance considerations (capacity factors, PPA/auction frameworks) into focus. Findings motivate a sequenced policy roadmap: regulatory stability, bankable PPAs, targeted grid upgrades, skills and supplier development, and pragmatic localization of components and services. Solar energy thus emerges not only as a clean electricity source but as an economic, environmental, and strategic lever for sustainable growth, energy security, and progress toward climate goals in the South Caucasus.